The lived experience of a foot burn injury from the perspective of seven Jordanians with diabetes: a hermeneutic phenomenological study - Abu‐Qamar, Maén Zaid (Int Wound J, 2011)
Poor vision and poor pain sensation expose sufferers of diabetes to foot burn injuries. A phenomenological approach was used to illuminate the lived experience of those with diabetes who sustained foot burn injuries. Face‐to‐face unstructured interviews were conducted with seven patients recruited from health care facilities throughout Jordan. The interviews were digitally recorded, transcribed verbatim into Arabic, checked for accuracy and then analysed using thematic analysis. Our study highlights that household appliances are a major cause of foot burn injuries among the studied population and that culturally specific risk factors predispose Jordanians with diabetes to foot burn injuries, namely ablution for males and cooking activities for females. Participants sought health care when home remedies failed. Inconsistent management practices were identified among health care providers. Culturally specific health education programs should be made to raise patients' awareness towards avoiding possible risks at home.